2013
DOI: 10.1021/jf403924c
|View full text |Cite
|
Sign up to set email alerts
|

Study on Human Intestinal BacteriumBlautiasp. AUH-JLD56 for the Conversion of Arctigenin to (−)-3′-Desmethylarctigenin

Abstract: Arctium lappa L. (A. lappa) is a popularly used vegetable as well as herbal medicine. Human intestinal microflora was reported to convert arctiin, the lignan compound with highest content in the dried fruits of Arctium lappa, to a series of metabolites. However, the specific bacterium responsible for the formation of 3'-desmethylarctigenin (3'-DMAG), the most predominant metabolite of arctiin by rat or human intestinal microflora, has not been isolated yet. In the present study, we isolated one single bacteriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 24 publications
0
20
1
Order By: Relevance
“…AUH-JLD56 has been shown to specifically and efficiently biotransform arctiin or arctigenin to (−)-3′-desmethyl arctigenin, which possesses good free radical-scavenging activity. 78 B. glucerasei sp. nov. HFTH-1 T produces a specific extracellular glucosylceramide enzyme that hydrolyzes glucosylceramide into functional substances with specific preventive effect against colon cancer (Table 4).…”
Section: Physiological Functions Of Blautia Biotransformation Of Bioactive Substances By Blautiamentioning
confidence: 99%
“…AUH-JLD56 has been shown to specifically and efficiently biotransform arctiin or arctigenin to (−)-3′-desmethyl arctigenin, which possesses good free radical-scavenging activity. 78 B. glucerasei sp. nov. HFTH-1 T produces a specific extracellular glucosylceramide enzyme that hydrolyzes glucosylceramide into functional substances with specific preventive effect against colon cancer (Table 4).…”
Section: Physiological Functions Of Blautia Biotransformation Of Bioactive Substances By Blautiamentioning
confidence: 99%
“…In addition, Escherichia coli MRY15-131 is a known pathogen to be colistin resistant ( Sekizuka et al, 2017 ). However, SNCE also inhibits OTU suspected to be beneficial, such as Blautia that converts the arctigenin contained in citrus to the sought-after 3′-desmethylarctigenin ( Liu et al, 2013 ) but tends to be lower in the SNCE group. SNCE also tends to decrease Lactobacillus amylovorus (although not significantly) and Lactobacillus delbrueckii , which are used as probiotics ( Omar et al, 2013 ; Yu et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies have shown that chemically synthesized arctigenin analogues exert strong anticarcinogenic activity (Cai et al, ; Lei et al, ). 3′‐DMAG is one of the arctigenin‐based structural analogues, but its anticancer activity has not been investigated (Liu et al, ; Wang, Solorzano, et al, ). In the present study, we compared cell proliferation inhibition by the 3′‐DMAG with that of arctigenin and found that 3′‐DMAG exerted more effective activity than arctigenin on HepG2 cells proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The same group has also reported that Blautia sp. AUH-JLD56 could biotransform arctin or arctigenin into 3′-DMAG (Liu et al, 2013;Wang, Yu, et al, 2017). They have evaluated the DPPH radical-scavenging activity of 3′-DMAG (Wang, Solorzano, et al, 2017), yet its anticancer activity remains unknown.…”
Section: Introductionmentioning
confidence: 99%